Adherence of the carriers of chronic renal disease to the conservative treatment - Medeiros, Maria Carolina Wanderley Costa de; Sá, Maria da Penha Carlos de (Rev Rene, 2011)
Chronic Kidney Disease (CKD) has currently been considered a public health problem. The delay in progression of CKD is a reality that can be achieved by monitoring these patients through a conservative treatment. Thus, this study aimed to evaluate the adherence of individuals to this treatment by analyzing the influence factors for this. To implement this analysis, we carried out a cross-sectional study involving 72 individuals with CKD stage IV accompanied at the nephrology clinic of the Hospital das Clínicas — UFPE. In this study, we found out that most of the interviewed patients have a low socioeconomic level and lots of difficulties to accomplish the diet and drug therapy. there is a real need to reformulate the treatment of these individuals, promoting a more interdisciplinary approach including educational activities.